Prevalence of depression, fatigue, and sleep disturbances in patients with myelopathy: Their relation with functional and neurological recovery - Menon, Nitin (J Spinal Cord Med, 2016)
OBJECTIVES: To observe the prevalence of fatigue, depression, and sleep disturbance in patients with myelopathy and their correlation with neurological and functional recovery. PATIENTS AND METHODS: Study conducted in a university tertiary research hospital with 127 patients with myelopathy (92 males) admitted to neurorehabilitation unit between January 2010 and December 2013. Mean age was 32.71 ± 13.08 years (range 15–65 years), and mean duration of injury was 76.22 ± 82.5 days (range 14–365 days). Functional status and impairments were assessed using Barthel Index and Spinal Cord Independence Measures. Depression, fatigue, and sleep disturbances were assessed using Hospital Anxiety and Depression Scale, Fatigue Severity Scale, and Pittsburgh Sleep Quality Index scales, respectively. Neurological recovery was assessed using American Spinal Injury Association's impairment scale. RESULTS: Forty-four out of 104 (42%) patients had borderline or confirmed depression, 36/108 (33%) had significant fatigue, and 62/106 (58%) had significant sleep disturbances at admission. Significant correlation was observed between change in fatigue and depression scores with change in functional status scores (P < 0.05) but no correlation (P > 0.05) between change in sleep disturbance scores and functional status score and neurological recovery (P > 0.05). Similarly, change in fatigue and depression scores had no correlation with neurological status improvement. Fatigue, depression, and sleep disturbance scores showed significant improvement, that is, admission vs. discharge scores (P < 0.05) with significant correlation between improvement in all three variables (P < 0.05). CONCLUSIONS: Study variables showed significant improvement in the present study with myelopathy patients but not necessarily correlating with functional and neurological recovery.